2022
DOI: 10.1177/17479541211070938
|View full text |Cite
|
Sign up to set email alerts
|

Strength and conditioning practices for the optimisation of speed and accuracy in cricket fast bowlers: A systematic review and meta-analysis

Abstract: The most important determinants of a cricket fast bowler's performance are bowling speed and accuracy. Even though various strength and conditioning practices (resistance, plyometric and modified-implement training) have been employed to improve these parameters, there is still ambiguity as to the effectiveness of such training programmes. This systematic review and meta-analysis examined the influence of various training interventions on fast bowling speed and accuracy. Searches were conducted across PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Lower-limb power in both the vertical and horizontal planes has been suggested to be important to cricket performance, irrespective of playing position, as explosive lower-limb power would be anticipated to aid in fielding, power-hitting and seam bowling [ 5 , 24 , 25 ]. Despite the proposed importance of lower-limb power for cricket performance, there was no differences in playing standard for either the broad jump or CMJ tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower-limb power in both the vertical and horizontal planes has been suggested to be important to cricket performance, irrespective of playing position, as explosive lower-limb power would be anticipated to aid in fielding, power-hitting and seam bowling [ 5 , 24 , 25 ]. Despite the proposed importance of lower-limb power for cricket performance, there was no differences in playing standard for either the broad jump or CMJ tests.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be linked to the moderately , non-significant, higher body mass recorded for professional cricketers in comparison to non-professional cricketers. It was anticipated that seam bowlers would possess higher levels of lower limb strength, as high force production capacity has been suggested as a pre-requisite for tolerating the high ground reaction forces experienced during the deliver stride, as well as to optimise ball release speed within male seam bowling scientific literature [ 24 , 27 ]. However, the results of the current investigation reported that non-seam bowlers possessed greater lower-limb strength.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis also reported that modified ball weight training had a moderate effect on bowling speed, albeit the findings being non-significant. 45 The reasons for the non-significant findings were at least partially attributed towards the difference in physical training background, skill level of the participants, and duration of the training program. With regards to the effects of modified ball weight training on bowling accuracy, the studies included in this systematic review reported contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…Lower-limb power in both the vertical and horizontal planes has been suggested to be important to cricket performance, irrespective of playing position, as explosive lower-limb power would be anticipated to aid in fielding, power-hitting and seam bowling [5,24,25]. Despite the proposed importance of lower-limb power for cricket performance, there was no…”
Section: Discussionmentioning
confidence: 99%